An update on intraoperative three-dimensional transesophageal echocardiography - Rong, Lisa Qia (Journal of Thoracic Disease, 2017)
Transesophageal echocardiography (TEE) was first used routinely in the operating rooms in the 1980s to facilitate surgical decision-making. Since then, TEE has evolved from the standard two-dimensional (2D) exam to include focused real-time three-dimensional (RT-3D) imaging both inside and outside the operating rooms. Improved spatial and temporal resolution due to technological advances has expedited surgical interventions in diseased valves. 3D imaging has also emerged as a crucial adjunct in percutaneous interventions for structural heart disease. With continued advancement in software, RT-3D TEE will continue to impact perioperative decisions.